Die akademische "Achse Berlin - Rom"? : der wissenschaftlich-kulturelle Austausch zwischen Italien und Deutschland 1920 bis 1945 - Albrecht, Andrea 1971- HerausgeberIn; Danneberg, Lutz 1951- HerausgeberIn; De Angelis, Simone 1965- HerausgeberIn; De Gruyter Oldenbourg (De Gruyter Oldenbourg, 2017)
"The Berlin-Rome Axis was more than a purely military project. In science and art as well, there were intensive if sometimes troubled cooperation. Many German Jews who had found refuge in Italy participated in this academic "axis" before their forced expulsion from Italy. In this volume, renowned experts analyze these networks of exchange. One message is clear: historians still have much to learn."--Provided by publisher